NORMAL STRESSES IN THE ELASTIC BODY WITH A LOCALLY CURVED COVERED FIBRE - Kosker, Resat; Simsek, Kadriye (YILDIZ TECHNICAL UNIV, 2007)
In the framework of the piecewise homogeneous body model with the use of the three-dimensional geometrically nonlinear exact equations of the theory of elasticity, the method developed for the determination of the stress distribution in the unidirectional fibrous composites with locally curved fibres is used to investigate normal stresses acting along the fibers for the case where there exists the bond covering cylinder with constant thickness between fiber and matrix materials are considered The case for which the interaction between the fibres is not taken into account is studied. The numerous numerical results related to the stress distribution in considered body and the influence of geometrical nonlinearity to this distribution are obtained and interpreted.
Keywords: Fibrous composite; local curving; covering material; geometrical nonlinearity; normal stresses; Engineering